Формування генеративних органів Quercus robur L. внаслідок ініціювання репродуктивного процесу - Krasnoshtan, I.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The formation of generative organs on the sprouts of juvenile trees of Quercus robur L. as a result of using the chlorcholinchloride water solution of different concentration in certain phenological phases of sprout growing has been researched. It has been determined that the chlorcholinchloride has a real influence on formation of female flowers and male floscules. After finishing the sprout growing when crowns of the researched trees were treated the female flowers and male floscules quantity was the highest. Different concentration of this substance determines various stimulative action on the formation of the female flowers and male floscules.